Coastal multi-hazard vulnerability assessment along the Ganges deltaic coast of Bangladesh - A geospatial approach - Ashraful Islam, M.; Mitra, D.; Dewan, Ashraf; Akhter, S. (Elsevier, 2016)
It is ironic that countries that are least responsible for or insignificant contributors to global climate change, are in fact, the most susceptible to its harmful impact. The Ganges deltaic coast, one of the largest sediment depocentres with the ~286 km long coastline of Bangladesh, faces a potentially multi-hazard threat due to climatic change. This study attempts to develop a coastal vulnerability index (CVI) by using seven physical parameters namely: (a) geomorphology; (b) coastal slope; (c) shoreline change rate; (d) rate of sea level change; (e) mean tide range; (f) bathymetry; and (g) storm surge height. These variables are considered as relative risk parameters and integrated through geospatial techniques (i.e., remote sensing and GIS), and then ranked to estimate the degree of coastline vulnerability to sea level rise. The entire coastline is ranked in accordance with multi-hazard vulnerability and the results reveal that 20.1% of the shoreline (57.9 km of total coastline in the Ganges delta) is very highly vulnerable, whilst 17.5% of shoreline (50.0 km) is estimated to be highly vulnerable. In contrast, 21.5% of the entire shoreline (61.3 km) is moderately vulnerable, whereas approximately 56.6 km (19.7%) and 60.4 km (21.2%) of the total shorelines are in low and very low vulnerability categories, respectively. The results of the CVI are expected to provide a clear picture for predicting future recession of shorelines; hence the outcome of this study can be used as an important tool by coastal managers for developing sustainable resources management practices. Furthermore, this study also offers a framework for prioritizing actions to enhance a community's resilience or to assist in developing appropriate adaptive measures as part of disaster risk reduction initiative.